2021
DOI: 10.1186/s13195-021-00938-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of potential modifications to Alzheimer’s disease clinical trials in response to disruption by COVID-19: a simulation study

Abstract: Background The COVID-19 pandemic disrupted Alzheimer disease randomized clinical trials (RCTs), forcing investigators to make changes in the conduct of such trials while endeavoring to maintain their validity. Changing ongoing RCTs carries risks for biases and threats to validity. To understand the impact of exigent modifications due to COVID-19, we examined several scenarios in symptomatic and disease modification trials that could be made. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many AD trial outcomes were successfully administered using telemedicine without compromise of data reliability 33 . Statistical modeling and trial simulation of AD trials indicated that stopping trials usually resulted in substantial loss of power and prolonging or enlarging trials were strategies to preserve trial integrity 34 . Despite the many challenges posed by the SARS‐CoV‐2 pandemic, the AD trial ecosystem proved to be resilient with few trials stopped during the pandemic and a substantial number of new trials initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Many AD trial outcomes were successfully administered using telemedicine without compromise of data reliability 33 . Statistical modeling and trial simulation of AD trials indicated that stopping trials usually resulted in substantial loss of power and prolonging or enlarging trials were strategies to preserve trial integrity 34 . Despite the many challenges posed by the SARS‐CoV‐2 pandemic, the AD trial ecosystem proved to be resilient with few trials stopped during the pandemic and a substantial number of new trials initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current model only describes mean behavior without accounting for inter‐subject variability and does not represent the mechanisms of the spatial spread of amyloid and tau 36,39,41 . Real‐world factors, such as missed dosing, unequal distributions of fast and slow progressors, and the potential effects of the COVID pandemic are also not accounted for in the present model 52 . To this end, a population‐based version of the Q‐ATN model incorporating actual dosing regimens, PK and PD modeling of gantenerumab, and inter‐subject variability in model parameters is currently in development.…”
Section: Discussionmentioning
confidence: 99%